Phacomorphic Glaucoma: An Easy Approach - Qamar, Abdul Rasheed (Pakistan Journal of Ophthalmology, 2007)
Purpose: To study an alternative method to reduce intraocular pressure in phacomorphic glaucoma at the time of cataract extraction. Design: This is a prospective interventional study from clinical practice. Material and Method: In 18 patients of phacomorphic glaucoma a modified controlled paracentesis was performed to decrease the intraocular pressure. Results: In all the patients the intraocular pressure was reduced, so that the cataract extraction could be performed immediately after the modified paracentesis.